Variations in the branching pattern of ventral branches of abdominal aorta- A cadaveric study - Sneha Sinha; Prerana Aggarwal; Jonaki Das Sarkar; Sri RamaTeja Allaboyina (Al Ameen Medical College, 2024)
Background: The three ventral branches of the abdominal aorta namely coeliac trunk (CT), superior mesenteric artery (SMA) and inferior mesenteric artery (IMA) are responsible for supplying blood to the derivatives of primitive foregut, midgut and hindgut respectively. Objectives: This study was conducted to assess the frequency of the variations of the ventral branches of Abdominal Aorta in the eastern part of the country. Methods: 39 cadavers of both genders and age ranging between 50 - 80 years were dissected. Origin, course and branching pattern of ventral branches of abdominal aorta were carefully observed, results tabulated and inference was drawn. Results: Variations found in 29 cadavers(74.35%) were right gastric artery (RGA) arising from the trunk of CT in 23% cadavers (12.8% males and 10.2% of the females), left inferior phrenic artery (LIPA) arising from CT found in 7.7% cadavers (5.1% males and 2.6% females ), right colic & ileocolic arising from an abnormal common branch (ACB) from right side of SMA found in 41% cadavers (23% males and 18% females) and CT & SMA arising from a common point from abdominal aorta found in 2.5% cadavers (2.5% males, no females). Conclusions: The knowledge of variations in Coeliac trunk is important for hepatic, gastric and splenic surgeries, that of Superior Mesenteric artery is important for intestinal surgeries.